Study of mild-moderate traumatic brain injury using tract-based spatial statistics (TBSS) and its relationship with cognitive function - Abdullah, Aimi Nadhiah (2023)
Traumatic brain injury (TBI) is known to lead to cognitive function impairment. The degree of impairment, however, varies depending on the severity and time post-TBI. Diffuse axonal damage has been discovered as the underlying pathology even in mild TBI. Thus, this study aims to determine the state of white matter putative connectivity in patients with mild-moderate TBI in the subacute phase, or within 10 weeks of injury, and its correlation to cognitive scores. A case-control prospective study was conducted involving 11 male patients with mild-moderate TBI and an age-matched control group of 11 adult male volunteers. Diffusion MRI scanning and cognitive testing were performed within 10 weeks of injury. The difference in fractional anisotropy (FA) values between TBI patients and control group was studied using tract-based spatial statistics (TBSS). Then, the FA values that were significantly different between patients and controls were correlated with neuropsychological tests in the TBI group. When comparing patients to the control group, several clusters with peak voxels of substantial FA reductions (p < 0.05) in the white matter skeleton were seen. These clusters were later treated as region of interest and were found in the superior fronto-occipital fasciculus, superior longitudinal fasciculus, uncinate fasciculus, and cingulum. White matter fibres in the region of the genu of the corpus callosum, anterior corona radiata, superior corona radiata, anterior thalamic radiation, and a portion of the inferior frontal gyrus also contained these clusters. Region of interest analysis revealed FA values significantly correlated with Malay version of Auditory Verbal Learning Test (MAVLT) immediate recall scores in the region of genu of corpus callosum (r = 0.62, p = 0.004) and right superior fronto-occipital fasciculus (r = 0.50, p = 0.026). Matrix-reasoning scores positively correlated with FA values in the region of right superior fronto-occipital fasciculus (r = 0.45, p = 0.045) and left anterior corona radiate (r = 0.47, p = 0.036), while having negative correlation in the region of right superior fronto-occipital fasciculus (r = -0.49, p = 0.030). Mean diffusivity (MD) values significantly have positive correlation with both Rey Complex Figure Tests (RCFT) immediate (r = 0.593, p = 0.015) and delayed (r = 0.640, p = 0.002) scores in the right superior longitudinal fasciculus. During the sub-acute phase of TBI, the mild-moderate TBI patients showed unusually decreased FA values and increase MD values compared to controls, which suggested disruption of white matter tracts. The correlation between FA values with neuropsychological scores further provide evidence of cognitive impairment probably responsible by the structural disruption.